Fistula in Ano-A 2-Year Prevalence Study on North Indian Rural Population - Neeru Kapur; Rajiv Kapur; Meghna Varma; Chakshu Batra; Bharat Bhushan Sharma (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Perianal fistula (PF) is a common inflammatory condition affecting the perianal region including the sphincter muscles, ischioanal fossae, and the perianal skin. It is notorious to recur and, as a result, causes significant morbidity in both urban and rural population. Magnetic resonance imaging (MRI) has revolutionized imaging in PFs as it provides excellent anatomical visualization of the fistulous tracts, their origin, course, number, chronicity, opening in the external and internal anal sphincter, length of sphincter, evidence of active disease and abscess formation along the tract. It is also very useful in presurgical mapping and reduce the chances of recurrence. Most of the studies done on PFs are based on the urban population. Rural population have a completely different lifestyle which makes them susceptible to various diseases, less prevalent in the urban population. Hence, the purpose of this article is to find the prevalence of different grades in North Indian rural region close to the NCR (National Capital Region). In the study including 98 patients, the maximum number of patients were classified into grade 1 and grade 4 by MRI according to St. James' University Hospital MRI classification. This is the second reported study on prevalence of different grades of PFs in rural population in India. The higher prevalence of grade 4 PFs in our study might be secondary to illiteracy, social stigma, poor hygiene, or higher recurrence rate. Closely understanding the difference in dynamics of urban and rural population, our goal of the study is to determine the prevalence of different grades of PFs in the rural population. We also aim to familiarize physicians, radiologists, and surgeons with the MRI evaluation and grading of PF to help in presurgical mapping and thus, reducing the chances of recurrence. We also recommend further studies to evaluate psycho-social factors as a barrier in seeking early medical care in rural population.